Meningkatkan Religiusitas, Nasionalisme serta Kedisiplinan Warga Sekolah Melalui Pembiasaan Positif - Fina Ismatul Uyun (MGMP PAI SMP BINTAN, 2023)
This best practice is focused on discussions related to positive habits as an effort to increase the religiosity, nationalism and discipline of school residents. So this research aims to explore the advantages of habituation carried out by state elementary school students in the Kaligawe Semarang area. Therefore, this research uses a qualitative approach. Data was collected through interviews, group discussions, observation and documentation. The results of data analysis show that students in this research sample have comfort in carrying out positive habits at school before learning begins. Islamic religious education is education that is closely related to the spiritual formation and character of students, so it is hoped that the results of this research can make a positive contribution to the development and strengthening of student character. The results of the research show that students in this research sample have their own comfort in getting used to it before studying. The advantages of habituation arise from the support of the school principal in the policy of developing habituation activities in schools, the role of creative and innovative teaching and education staff in developing habituation through various activities, the younger generation who have religious insight and school culture.